Assessment of Gene Expression on the Gap Junction Connexin of Cumulus Cells on Infertile Women With Polycystic Ovary Syndrome and Poor Ovarian Response: The Novel Role of Propranolol - Farideh Zangeneh; Mohammad Mehdi Naghizadeh; Mina Jafarabadi; Masoumeh Dehghan; Maryam Bagheri (Journal of Family and Reproductive Health)
Objective: Building upon prior research, our investigation focused on examining changes in gene expression of Connexins 37 and 43 (Cx) influenced by β2-adrenergic agents in cumulus cell cultures from women with polycystic ovarian syndrome (PCOS) and poor ovarian response (POR), all of whom were candidates for in vitro fertilization (IVF). Materials and methods: This experimental study was conducted between April 2021 and November 2023, involving three groups: a control group (donated eggs) and two study groups (POR and PCO). All three groups received ovulation stimulation drugs. Following oocyte puncture, cumulus cells (CCs) were isolated and placed in a culture medium. After three passages, CCs were exposed to the ADR-β2 agonist isoproterenol and its antagonist propranolol (100nM for both drugs). RNA extraction was performed, and cDNA was synthesized. Real-time PCR was used to determine gene expression, and protein levels were measured through the Western blotting method. Results: The gene expression of Cx 37/43 was significantly reduced in all three groups (P<0.001). For women with PCO and POR, Isop notably decreased expressions (P<0.001), while Prop increased them (P<0.001). Western Blot results confirmed these findings. Conclusion: The findings of this in-vitro study suggest that the beta-2 adrenergic antagonist propranolol could upregulate gene expression of Cx37/43 in the cellular connections of CCs among infertile women. Consequently, propranolol may enhance communication between CCs and oocytes, facilitating the transfer of signalling messengers and other essential agents required for oocyte development. This novel discovery could have significant implications for oocyte growth and maturation, offering valuable perspectives on drug treatment and assisted reproductive technology. This novel discovery could have significant implications for oocyte growth and maturation, offering valuable perspectives on drug treatment and assisted reproductive technology.